Painting On Stone As A Learning Media For Fine Arts To Improve Students' Creativity At Sdn 24 Ampenan - Tesa Yustika; Babat Nufus Tarenaksa (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Visual arts education in elementary schools plays a crucial role in developing students' creativity, imagination, and expressive abilities. This study aims to explore the use of stones as a painting medium in art education and its impact on enhancing the creativity of elementary school students. Stones were chosen as an alternative medium due to their easy availability in the surrounding environment, diverse shapes and textures, and their ability to stimulate students’ creative potential in producing artworks. This research adopts a descriptive qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation of student artworks.The findings reveal that the use of stones as a painting medium significantly enhances students’ enthusiasm, active participation, and creativity in the art learning process. Students feel challenged to adapt their designs to the natural shapes of the stones, which encourages the development of original and flexible visual ideas. Additionally, this activity strengthens the connection between art and the environment while fostering ecological awareness from an early age. Teachers also found this method beneficial as a more contextual and enjoyable learning alternative. Based on these findings, it is recommended that art teachers integrate stone media into learning activities to enrich students’ aesthetic experiences. This study also opens opportunities for the development of more innovative and locally grounded art curricula.